2012
DOI: 10.1016/j.schres.2012.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted cognitive remediation for schizophrenia: A randomized single-blind pilot study

Abstract: Cognitive impairment is a core symptom in schizophrenia that has a significant impact on psychosocial function, but shows a weak response to pharmacological treatment. Consequently, a variety of cognitive remediation strategies have been evaluated to improve cognitive function in schizophrenia. The efficacy of computer-based cognitive remediation as a stand-alone intervention on general measures of neuropsychological function remains unclear. We tested the effectiveness of biweekly training using computerized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 43 publications
2
47
0
Order By: Relevance
“…Two other studies [37,38] that were published before our publication period showed improved verbal memory and auditory neural responses (M100) after intensive auditory training. The MEG findings contradict Rass et al's study [36], but are in line with the original neuroplasticity-based studies from Fisher and colleagues [34,39], which reported significant improvements in verbal learning and memory and global cognition, and maintenance of treatment gains at 6- month follow-up. Thus, the limited data available for this review suggest neuroplasticity-based interventions likely impact functional brain changes associated with basic perceptual/cognitive processes.…”
Section: Neuroplasticity-based Approachessupporting
confidence: 80%
See 1 more Smart Citation
“…Two other studies [37,38] that were published before our publication period showed improved verbal memory and auditory neural responses (M100) after intensive auditory training. The MEG findings contradict Rass et al's study [36], but are in line with the original neuroplasticity-based studies from Fisher and colleagues [34,39], which reported significant improvements in verbal learning and memory and global cognition, and maintenance of treatment gains at 6- month follow-up. Thus, the limited data available for this review suggest neuroplasticity-based interventions likely impact functional brain changes associated with basic perceptual/cognitive processes.…”
Section: Neuroplasticity-based Approachessupporting
confidence: 80%
“…One reported significant effects, in terms of normalized magnetoencephalography (MEG) sensory gating (M50 ratio) following neuroplasticity-based CR training [32]; in a separately published re-examination of the data, the researchers found normalized alpha desynchronization mediated the effects of improved auditory gating [35]. The other study concluded there were no gains in neurocognition and no changes in electroencephalogram (EEG) measures following 40 hours of BrainFitness training [36]. Two other studies [37,38] that were published before our publication period showed improved verbal memory and auditory neural responses (M100) after intensive auditory training.…”
Section: Neuroplasticity-based Approachesmentioning
confidence: 99%
“…Keefe et al 39 also reported nonsignificant results from the multisite Cognitive Remediation in the Schizophrenia Trials Network study, which used brain fitness training within the CR arm in a pilot efficacy RCT. Finally, Rass et al 40 found no significant improvement in cognitive or event-related potential outcome measures following the standard program package of brain fitness training.…”
Section: Trends In Restorative Cognitive Trainingmentioning
confidence: 97%
“…[9][10][11][12][13] Four other studies have investigated this form of training in schizophrenia, but methodologies and results have been inconsistent across studies. [14][15][16][17] While some of the findings have been promising, the discrepancies indicate the need for additional research.…”
Section: Introductionmentioning
confidence: 99%